2020
DOI: 10.3390/mi11010057
|View full text |Cite
|
Sign up to set email alerts
|

A Low Contact Impedance Medical Flexible Electrode Based on a Pyramid Array Micro-Structure

Abstract: Flexible electrodes are extensively used to detect signals in electrocardiography, electroencephalography, electro-ophthalmography, and electromyography, among others. These electrodes can also be used in wearable and implantable medical systems. The collected signals directly affect doctors’ diagnoses of patient etiology and are closely associated with patients’ life safety. Electrodes with low contact impedance can acquire good quality signals. Herein, we established a method of arraying pyramidal microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…To the best of our knowledge, we utilized electrodeposition and optimized the process parameters to maximize the surface area of the skin electrode for the first time. Our electrodeposition approach exhibits superior surface area enlargement compared to previous skin electrode studies implementing microstructures, , which increased the surface area by only 1.11 times.…”
Section: Results and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To the best of our knowledge, we utilized electrodeposition and optimized the process parameters to maximize the surface area of the skin electrode for the first time. Our electrodeposition approach exhibits superior surface area enlargement compared to previous skin electrode studies implementing microstructures, , which increased the surface area by only 1.11 times.…”
Section: Results and Discussionmentioning
confidence: 82%
“…Furthermore, we demonstrated the superiority of the ESASE on bioelectric signal analysis through muscle fatigue estimation with EMG measurements. Muscle fatigue estimation is one of the most representative applications of EMG signal analysis. As the EMG analysis can conveniently provide the physiological status of muscles in real time, several recent studies utilized the noninvasive EMG technique for continuous muscle fatigue monitoring. Muscle fatigue can be estimated by analyzing the frequency components of the measured EMG. It has been known that the portion of low-frequency EMG signals increases when the muscle gets tired. Because previous skin electrodes showed low SNR and nonconformal contact properties, reliable EMG analyses were difficult .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In another study, Wang et al investigated the fabrication of a microelectrode array in the form of pyramidal microstructures on a polydimethylsiloxane (PDMS) substrate with a parylene transition layer between the electrode and the substrate [ 4 ]. Their results showed that this method of fabrication can increase the contact area of the electrodes, enhance the bonding force between the substrate and the electrodes, and reduce the electrode impedance as well as the electrode–skin contact impedance.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…In this editorial note, we briefly review the major findings of the 10 articles published in the Special Issue on microelectrode arrays and application to medical devices. The articles are categorized into three sections, i.e., fabrication techniques [ 1 , 2 , 3 , 4 ], application demonstration [ 5 , 6 , 7 , 8 ], and review of recent advances in this field [ 9 , 10 ].…”
mentioning
confidence: 99%
“…To overcome these limitations, EDA sensors based on dry electrodes have been developed. To minimize obstructiveness, they tend to measure EDA from different locations on the body rather than the palms, including the wrists [8][9][10][11] , the forearms 12 , the shoulders 8 , and even the back 13 . However, when measured off the palms, the EDA signals can be contaminated or even interrupted by accumulative sweat secreted from the apocrine sweat glands due to the thermo-regulation of our body, an effect that is only negligible at the palmar and the plantar regions 14 .…”
mentioning
confidence: 99%